Oxygen carrying silicone hydrogel contact lens material, process for its production and use

CN117247491BActive Publication Date: 2026-10-09NANJING RUIJIE MEDICAL TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211644611.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-16
Publication Date
2026-10-09
Estimated Expiration
2042-12-16

AI Technical Summary

Technical Problem

该专利提供的角膜接触镜制备方法,所得镜片透氧率高,由其制成的隐形眼镜表面湿润性好,柔软度高,可增强佩带的舒适性,但是无法携带、释放O2,所以,开发一种携氧并释放O2的硅水凝胶接触镜材料及其生产工艺十分重要

Benefits of technology

[0034] 1. This invention is the first to propose a contact lens that carries oxygen and releases O2, reducing eye edema. The material used, perfluorotripropylamine, has a superior ability to dissolve gases. Its oxygen content is proportional to the oxygen partial pressure. Under the same oxygen partial pressure, its oxygen carrying capacity is about 20-25 times that of water and blood plasma. After being emulsified with a surfactant, it has the property of dissolving oxygen and the ability to diffuse oxygen to tissues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117247491B_ABST
    Figure CN117247491B_ABST
Patent Text Reader

Abstract

The application discloses an oxygen-carrying type silicon hydrogel contact lens material and a production process and application thereof, and the oxygen-carrying type silicon hydrogel contact lens material comprises the following raw materials in parts by weight: emulsified perfluorocarbon 1-10 parts, hydrophilic monomer 40-80 parts, siloxane monomer 20-40 parts, initiator 0.5-2 parts and crosslinking agent 0.5-2 parts. The surface active agent emulsified perfluorotripropylamine used in the oxygen-carrying type silicon hydrogel contact lens material has the properties of dissolving oxygen and the ability of supplying oxygen to tissues, and has excellent biocompatibility, thereby meeting the daily wearing demand; the oxygen-carrying type silicon hydrogel contact lens material can also carry and release O2, has the effect of preventing edema and other complications caused by eye hypoxia, and has the advantages of simple production process, practicality, initiation of polymerization under ultraviolet light irradiation, rapid and efficient monomer reaction and good oxygen carrying and releasing capacity of prepared lens material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical materials technology, specifically relating to an oxygen-carrying silicone hydrogel contact lens material, its production process, and its application. Background Technology

[0002] Oxygen is essential for the cornea to maintain normal metabolic activity and structural integrity. Since the cornea lacks blood vessels to supply the oxygen needed for normal cellular metabolism, its oxygen supply primarily comes from the air. Contact lenses act as a barrier between the cornea and its oxygen supply. Continuous wear of contact lenses can easily lead to corneal hypoxia, causing corneal edema, dry eyes, discomfort, and even congestion; in severe cases, it can result in blurred vision. Therefore, contact lenses must have excellent oxygen permeability.

[0003] Silicone hydrogel is a hydrophilic organic polymer material with a honeycomb structure. The larger silica groups within it possess excellent oxygen permeability, allowing oxygen to be transported through both the silicone and hydrogel phases, resulting in superior oxygen permeability. Silicone hydrogel contact lenses combine the high oxygen permeability of silicone with the softness of traditional hydrogel lenses, meeting the requirements for high oxygen permeability during extended wear while also providing excellent wearing comfort.

[0004] Perfluorinated carbon (PFC) is a hydrocarbon in which all or part of the hydrogen atoms are replaced by fluorine atoms. It is chemically inert and biocompatible. Although insoluble in water, it can dissolve large amounts of gas. Its oxygen content is directly proportional to its oxygen partial pressure; at the same oxygen partial pressure, its oxygen-carrying capacity is approximately 20-25 times that of water and blood plasma. After emulsification with surfactants, it possesses the property of dissolving oxygen and the ability to supply oxygen to tissues through diffusion. This high oxygen-carrying capacity makes PFC a promising candidate for applications in the biomedical field.

[0005] The prior art, CN 112812243 A, discloses an oxygen-permeable fluorosilicone hydrogel contact lens and its preparation method. The composition used includes three fluorosiloxane polymer monomers, a hydrophilic monomer, and a crosslinking agent, and may also contain other additives. The composition is cured by thermally initiated polymerization, followed by demolding, extraction, and sterilization to obtain the lens. The corneal contact lens preparation method provided by this patent results in lenses with high oxygen permeability, good surface wettability, and high softness, which can enhance wearing comfort. However, it cannot carry or release O2. Therefore, it is very important to develop a silicone hydrogel contact lens material that carries and releases O2 and its manufacturing process. Summary of the Invention

[0006] Objective of the Invention: To address the problems existing in the prior art, this invention provides an oxygen-carrying silicone hydrogel contact lens material that can carry and release O2, offering high wearing comfort. This oxygen-carrying silicone hydrogel contact lens material not only possesses excellent biocompatibility, meeting the needs of daily wear, but also carries and releases O2, effectively preventing edema and other complications caused by ocular hypoxia.

[0007] The present invention also provides a manufacturing process and application of the oxygen-carrying silicone hydrogel contact mirror material.

[0008] Technical Solution: To achieve the above objectives, this invention provides an oxygen-carrying silicone hydrogel contact lens material, comprising the following raw materials in parts by weight: 1-10 parts of surfactant-emulsified perfluorinated carbon, 40-80 parts of hydrophilic monomer, 20-40 parts of siloxane monomer, 0.5-2 parts of initiator, and 0.5-2 parts of crosslinking agent. The emulsifier used in the emulsification process is a surfactant, human serum albumin, or phospholipid.

[0009] Preferably, the emulsifier is the surfactant Pluronic F-127.

[0010] The perfluorocarbon compound is perfluorotripropylamine, with the following structure:

[0011]

[0012] The weight ratio of perfluorocarbon compound to emulsifier in the surfactant-emulsified perfluorocarbon is 0.1 to 1:1.

[0013] The hydrophilic monomer is one or more of polyvinyl alcohol, methyl methacrylate, hydroxyethyl methacrylate, and N-vinylpyrrolidone; the siloxane monomer is a silane coupling agent containing Si-O-Si bonds.

[0014] Preferably, the hydrophilic monomers are hydroxyethyl methacrylate and N-vinylpyrrolidone.

[0015] Preferably, the siloxane monomer is 3-methacryloyloxypropyltrimethoxysilane.

[0016] The initiator is any one of azo initiator, 2-hydroxy-2-methyl-1-phenylpropanone, and benzophenone; the crosslinking agent is any one of ethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, and N,N-methylenebisacrylamide.

[0017] Preferably, the initiator is 2-hydroxy-2-methyl-1-phenylpropanone.

[0018] Preferably, the crosslinking agent is N,N-methylenebisacrylamide.

[0019] The manufacturing process of the oxygen-carrying silicone hydrogel contact lens material of the present invention includes the following steps:

[0020] (1) Oxygenated mixing of raw materials: The perfluorocarbon solution emulsified with surfactant is added to the prepolymer substrate after oxygenation, and the mixture is stirred and oxygenated to make the components evenly mixed to obtain the reaction stock solution; the prepolymer substrate is prepared by mixing hydrophilic monomers and siloxane monomers, and then adding initiator and crosslinking agent and stirring.

[0021] (2) Curing and molding: Take the original liquid from step (1) and drop it into the concave mold. After UV irradiation, insert the convex mold into the concave mold and continue UV irradiation. After the liquid is completely cured and molded, turn off the UV and let it stand at room temperature.

[0022] (3) Elution: After standing, the material is demolded, soaked, and extracted with organic solvent to remove unreacted monomers or oligomers, thus obtaining oxygen-carrying silicone hydrogel contact mirror material.

[0023] In step (1), the weight ratio of the hydrophilic monomer to the siloxane monomer is 2-5:1-3; the first oxygenation lasts for 10-20 minutes, and the second oxygenation lasts for 30-40 minutes.

[0024] In step (2), the first ultraviolet (31-40w) irradiation lasts for 1-2 minutes; the second ultraviolet (31-40w) irradiation lasts for 8-10 minutes.

[0025] Preferably, the prepolymer substrate in step (1) is made by mixing 40 parts by weight of hydrophilic monomer hydroxyethyl methacrylate, 40 parts by weight of N-vinylpyrrolidone, 20 parts by weight of siloxane monomer 3-methacryloyloxypropyltrimethoxysilane, and then adding 1 part by weight of photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone and 0.8 parts by weight of crosslinking agent N,N-methylenebisacrylamide, and stirring at room temperature.

[0026] Furthermore, the organic solvent in step (3) is any one of hexane, ethanol, methanol, and isopropanol.

[0027] Preferably, the organic solvent in step (3) is ethanol.

[0028] The application of the oxygen-carrying silicone hydrogel contact lens material described in this invention in the preparation of contact lenses that carry and release oxygen slowly.

[0029] The oxygen-carrying silicone hydrogel contact lens material described in this invention has applications in the biomedical field, such as carrying oxygen and releasing O2, and reducing eye edema.

[0030] The application of the silicone hydrogel contact lens material described in this invention in the preparation of contact lenses that carry oxygen and release O2, and reduce eye edema.

[0031] Existing technologies typically use fluorosiloxanes as polymer monomers to improve the oxygen permeability and hydrophilicity of silicone hydrogel lenses. However, the monomers themselves do not have the ability to dissolve and carry oxygen. This invention, based on a siloxane monomer with good oxygen permeability, adds perfluorotripropylamine, which has excellent biocompatibility and oxygen-dissolving properties. After emulsification with a surfactant, it forms nanoparticles that can be loaded into the contact lens substrate. After oxygenation, these nanoparticles dissolve and carry oxygen, enabling oxygen release into the eye. This is the first time that perfluorocarbon compounds have been applied to contact lens materials, utilizing their oxygen-dissolving properties to achieve oxygen release into the eye. Furthermore, the production process provided by this invention is simple and efficient. The oxygen-carrying silicone hydrogel contact lens material can be obtained through three processes: raw material oxygenation and mixing, curing and molding, and elution. The production process is compatible with existing contact lens material production equipment, significantly reducing equipment upgrade costs and offering high operability.

[0032] The emulsifier used in this invention, such as the surfactant Pluronic-F127, possesses unique amphiphilic properties. This dual hydrophilic and lipophilic nature allows it to better reduce surface tension and achieve optimal emulsification. Perfluorotripropylamine is an important perfluorotertiary amine compound with good heat resistance and excellent biocompatibility. Its strong CF bonds give it superior gas-dissolving capacity; under the same oxygen partial pressure, its oxygen-carrying capacity is approximately 20-25 times that of water and blood plasma. Compared to other emulsifiers, perfluorotripropylamine emulsified with Pluronic-F127 can form uniformly dispersed nanoparticles, maintaining the stability of both phases when added to the prepolymer substrate. It is speculated that the better effect of perfluorotripropylamine compared to other perfluorinated compounds may be due to its higher fluorine-carbon atom ratio and lower boiling point, resulting in a higher amount of dissolved oxygen in the emulsion. Since the gas exchange capacity of perfluorocarbon compounds is determined by the total oxygen content in the emulsion, perfluorotripropylamine exhibits significant effects.

[0033] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0034] 1. This invention is the first to propose a contact lens that carries oxygen and releases O2, reducing eye edema. The material used, perfluorotripropylamine, has a superior ability to dissolve gases. Its oxygen content is proportional to the oxygen partial pressure. Under the same oxygen partial pressure, its oxygen carrying capacity is about 20-25 times that of water and blood plasma. After being emulsified with a surfactant, it has the property of dissolving oxygen and the ability to diffuse oxygen to tissues.

[0035] 2. In this invention, both perfluorotripropylamine, which serves as the oxygen carrier, and the surfactant have excellent biocompatibility. When combined with the contact lens substrate, oxygen can be dissolved and carried after oxygenation, thus releasing oxygen into the eye. This reduces corneal hypoxia-induced eye edema when wearing contact lenses and helps prevent eye complications.

[0036] 3. The production process provided by this invention is simple and efficient. The oxygen-carrying silicone hydrogel contact lens material can be obtained through three steps: oxygenation and mixing of raw materials, curing and molding, and elution. The production process is compatible with existing contact lens material production equipment, greatly reducing equipment upgrade costs and making it highly operable. Attached Figure Description

[0037] Figure 1 This is a transmission image of Example 1;

[0038] Figure 2 The proportion of main elements in Example 4;

[0039] Figure 3 The X-ray photoelectron spectroscopy peak diagram of fluorine in Example 4;

[0040] Figure 4 The dissolved oxygen diagram is from Example 6;

[0041] Figure 5 The dissolved oxygen diagram for Example 7;

[0042] Figure 6 This is a dissolved oxygen diagram for Example 8. Detailed Implementation

[0043] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.

[0044] Unless otherwise specified, the experimental methods described in the embodiments are conventional methods; unless otherwise specified, the reagents and materials are commercially available.

[0045] Example 1

[0046] Preparation of perfluorotripropylamine nanoparticles emulsified with surfactant Pluronic-F127

[0047] A 1% (w / w) aqueous solution of surfactant Pluronic-F127 (sigma, CAS: 9003-11-6) was mixed with perfluorotripropylamine at a weight ratio of 1:1 and sonicated for 10 min to obtain a white emulsion.

[0048] Example 2

[0049] The method of Example 1 is used, except that the emulsifier added in Example 1 is 1% human serum albumin solution (Yuan Ye, CAS: 70024-90-7).

[0050] Example 3

[0051] The method of Example 1 is used, except that the emulsifier added in Example 1 is a 1% phospholipid solution (Maclean, CAS: 63-89-8).

[0052] The perfluorotripropylamine emulsions prepared in Examples 1-3 and emulsified with different emulsifiers were allowed to stand for 10 minutes to observe their stability. The emulsions were then mixed with the prepolymer substrate and stirred for 40 minutes to observe the transparency of the mixture in order to select the optimal emulsifier. The prepolymer substrate was prepared by mixing 40 parts by weight of hydrophilic monomer hydroxyethyl methacrylate, 40 parts by weight of N-vinylpyrrolidone, and 20 parts by weight of siloxane monomer 3-methacryloyloxypropyltrimethoxysilane (CAS: 2530-85-0), then adding 1 part by weight of photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone and 0.8 parts by weight of crosslinking agent N,N-methylenebisacrylamide and mixing them evenly. Finally, 10 parts by weight of the above emulsion were added.

[0053] Table 1. Solution states of emulsions in Examples 1-3

[0054] Example 1 Stablize transparent Example 2 Stablize turbid Example 3 Poor turbid

[0055] As shown in Table 1, the perfluorotripropylamine emulsions prepared in Examples 1 and 2 exhibit better stability compared to Example 3. Furthermore, when the emulsions from Examples 1 and 2 are mixed with the prepolymer substrate, the mixture from Example 1 better meets the production requirements of silicone hydrogel contact mirror materials. It is speculated that the better emulsification effect of Example 1 is due to the unique amphiphilic nature of the surfactant Pluronic-F127. This property, being both hydrophilic and lipophilic, allows it to better reduce surface tension, achieving optimal emulsification. Its addition to the prepolymer substrate maintains the stability of both phases, meeting the requirements of the next production step. Figure 1 As shown, the perfluorotripropylamine solution emulsified with the surfactant Pluronic-F127 can form uniformly dispersed nanoparticles with a particle size of about 50 nm.

[0056] Example 4

[0057] Manufacturing process of oxygen-carrying silicone hydrogel contact lens material

[0058] (1) Oxygenation mixing of raw materials: Take 10 parts of the emulsion in Example 1 above and oxygenate (high pressure oxygen cylinder) for 20 minutes. Add the prepolymer substrate (the composition of the prepolymer substrate and the weight ratio of the prepolymer substrate to the emulsion are the same as in Example 3). Continue to stir magnetically and oxygenate for 40 minutes to make the components evenly mixed and obtain the reaction stock solution.

[0059] (2) Curing and molding: Take 200 μL of the original liquid from step (1) and drop it into the concave mold. After irradiating with ultraviolet light (power of 36w) for 1 min, insert the convex mold into the concave mold and continue to irradiate with ultraviolet light (power of 36w) for 8 min. After the liquid has completely cured and molded, turn off the ultraviolet light and let it stand at room temperature for 5 min.

[0060] (3) Elution: After standing, the material is demolded, soaked, and extracted with ethanol to remove unreacted monomers or oligomers, thus obtaining oxygen-carrying silicone hydrogel contact mirror material.

[0061] Depend on Figure 2 , 3 The elemental composition and elemental state information of the prepared silicon hydrogel contact mirror material were obtained from X-ray photoelectron spectroscopy (XPS) data. Figure 2 It can be seen that the material prepared in Example 4 contains silicon (Si) and fluorine (F) as the main elements, indicating that the perfluorotripropylamine nanoparticles emulsified with the surfactant Pluronic-F127 obtained in Example 1 were successfully loaded into the silicon hydrogel contact mirror material. Figure 3 After peak fitting of the XPS of F1s, the elemental information of organic fluorine (characteristic peak at 689.20 eV) was obtained, which further illustrates that the perfluorotripropylamine nanoparticles emulsified by the surfactant Pluronic-F127 loaded on the silicone hydrogel contact mirror material are not easily washed away, thus better carrying and releasing O2.

[0062] Example 5

[0063] The method of Example 4 was used, except that the weight ratio of the emulsion added in Example 1 was perfluorotripropylamine: 1% of the surfactant Pluronic-F127 aqueous solution = 0.2:1, to obtain the silicone hydrogel contact mirror material.

[0064] Comparative Example 1

[0065] The method of Example 4 is used, except that oxygenation is not performed in step (1).

[0066] Comparative Example 2

[0067] The method of Example 4 was used, except that the perfluorinated compound added in Example 1 was perfluorotributylamine, and a silicone hydrogel contact mirror material was obtained.

[0068] Comparative Example 3

[0069] The method of Example 4 was used, except that the perfluorinated compound added in Example 1 was perfluoronaphthalene, and a silicon hydrogel contact mirror material was obtained.

[0070] Example 6

[0071] The dissolved oxygen content of the silicone hydrogel contact lens material obtained in Example 4 was measured. The specific steps are as follows: 20 mL of distilled water was placed in a sealed flask equipped with a dissolved oxygen electrode (Leici, JPBJ-608 portable dissolved oxygen meter), and N2 was introduced for deoxygenation. After deoxygenation was completed, 20 prepared silicone hydrogel contact lens pieces were added to the deoxygenated water, and the dissolved oxygen content in the water was measured after 24 hours. The dissolved oxygen data was calculated using the formula: dissolved oxygen content (mg / kg) = 0.02 L * final dissolved oxygen value (mg / L) / total weight (kg).

[0072] Example 7

[0073] The dissolved oxygen content of the silicon hydrogel contact mirror material obtained in Example 5 was measured, following the same steps as in Example 6.

[0074] Example 8

[0075] The dissolved oxygen content of the silicon hydrogel contact mirror material obtained in Comparative Example 1 was measured, following the same steps as in Example 6.

[0076] Example 9

[0077] The dissolved oxygen content of the silicon hydrogel contact mirror material obtained in Comparative Example 2 was measured, and the specific steps were the same as in Example 6.

[0078] Example 10

[0079] The dissolved oxygen content of the silicon hydrogel contact mirror material obtained in Comparative Example 3 was measured, and the specific steps were the same as in Example 6.

[0080] Depend on Figure 4-6As shown in Table 2, when the silicone hydrogel contact lens materials prepared in Examples 4-5 and Comparative Examples 1-3 were added to the prepared deoxygenated water, the dissolved oxygen content in the water increased within 24 hours. This indicates that the silicone hydrogel contact lens materials loaded with perfluoride nanoparticles all have a certain ability to carry and release oxygen. The data in Table 2 show that the dissolved oxygen content in the water after 24 hours for the contact lens material prepared in Example 4 was much higher than that in Comparative Examples 2 and 3. This indicates that, compared to other perfluorides, only perfluorotripropylamine has a better ability to dissolve and carry oxygen in the production process of silicone hydrogel contact lenses, significantly exceeding other perfluorides. Furthermore, under the same conditions as in Example 4, when perfluoropentane, perfluorohexane, perfluorooctane, perfluorooctylbromide, perfluoro1,8-dichlorooctane, etc., were used, the average dissolved oxygen content did not exceed 80 (mg / kg), further demonstrating the importance of perfluorotripropylamine in this invention.

[0081] Depend on Figure 4-6 As shown in Table 2, within 30 minutes, the oxygen carried in Examples 6-8 exhibited a rapid release and dissolution process, which subsequently slowed down. Furthermore, compared to Example 7, Example 6 had a higher weight percentage of perfluorotripropylamine, resulting in a stronger ability to dissolve and carry oxygen. In contrast to Example 6, Example 8 did not involve oxygenation during its preparation process, and the measured data was significantly lower than the dissolved oxygen content of the silicone hydrogel contact mirror material prepared in Example 6 through oxygenation mixing, curing, and elution processes. This highlights the importance of a complete production process in the preparation of oxygen-carrying silicone hydrogel contact materials.

[0082] Table 2 Dissolved oxygen data for contact lens materials in Examples 6-10

[0083]

[0084] Example 11

[0085] Manufacturing process of oxygen-carrying silicone hydrogel contact lens material

[0086] (1) Oxygenation mixing of raw materials: Take 1 part by weight of the emulsion in Example 1 above and oxygenate it (high pressure oxygen cylinder) for 10 min. Add the prepolymer substrate (40 parts by weight of methyl methacrylate, 20 parts by weight of siloxane monomer 3-methacryloyloxypropyltrimethoxysilane mixed evenly, then add 0.5 parts of photoinitiator benzophenone and 0.5 parts of crosslinking agent ethylene glycol dimethacrylate mixed evenly). Continue to stir magnetically and oxygenate for 30 min to make the components evenly mixed and obtain the reaction stock solution.

[0087] (2) Curing and molding: Take 200 μL of the original liquid from step (1) and drop it into the concave mold. After irradiating with ultraviolet light (power of 40w) for 2 minutes, insert the convex mold into the concave mold and continue to irradiate with ultraviolet light (power of 40w) for 10 minutes. After the liquid is completely cured and molded, turn off the ultraviolet light and let it stand at room temperature for 5 minutes.

[0088] (3) Elution: After standing, the material is demolded, soaked, and extracted with ethanol to remove unreacted monomers or oligomers, thus obtaining oxygen-carrying silicone hydrogel contact mirror material.

[0089] Example 12

[0090] Manufacturing process of oxygen-carrying silicone hydrogel contact lens material

[0091] (1) Oxygenation mixing of raw materials: Take 10 parts by weight of the emulsion in Example 1 above and oxygenate (high pressure oxygen cylinder) for 20 min. Add the prepolymer substrate (80 parts by weight of hydroxyethyl methacrylate, 40 parts by weight of siloxane monomer 3-methacryloyloxypropyltrimethoxysilane are mixed evenly, and then add 2 parts of photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone and 2 parts of crosslinking agent triethylene glycol dimethacrylate are mixed evenly). Continue to stir magnetically and oxygenate for 30 min to make the components evenly mixed and obtain the reaction stock solution.

[0092] (2) Curing and molding: Take 200 μL of the original liquid from step (1) and drop it into the concave mold. After irradiating with ultraviolet light (power of 36w) for 1 min, insert the convex mold into the concave mold and continue to irradiate with ultraviolet light (power of 36w) for 10 min. After the liquid has completely cured and molded, turn off the ultraviolet light and let it stand at room temperature for 5 min.

[0093] (3) Elution: After standing, the material is demolded, soaked, and extracted with ethanol to remove unreacted monomers or oligomers, thus obtaining oxygen-carrying silicone hydrogel contact mirror material.

Claims

1. An oxygen-carrying silica hydrogel contact lens material, characterized in that, The oxygen-carrying silicone hydrogel contact lens material comprises the following raw materials in parts by weight: 1-10 parts of emulsified perfluorinated carbon, 40-80 parts of hydrophilic monomer, 20-40 parts of siloxane monomer, 0.5-2 parts of initiator, and 0.5-2 parts of crosslinking agent; the emulsified perfluorinated carbon is prepared by mixing a 1% (w / w) aqueous solution of surfactant Pluronic-F127 with perfluorotripropylamine at a weight ratio of 1:1, and sonicating for 10 min to obtain a white emulsion; wherein, the surfactant Pluronic-F127 is from Sigma, CAS: 9003-11-6.

2. The oxygen-carrying silica hydrogel contact mirror material according to claim 1, characterized in that, The hydrophilic monomer is one or more of hydroxyethyl methacrylate and N-vinylpyrrolidone; the siloxane monomer is a silane coupling agent containing Si-O-Si bonds.

3. The oxygen-carrying silica hydrogel contact mirror material according to claim 1, characterized in that, The initiator is any one of azo initiator, 2-hydroxy-2-methyl-1-phenylpropanone, and benzophenone; the crosslinking agent is any one of ethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, and N,N-methylenebisacrylamide.

4. A manufacturing process for the oxygen-carrying silicone hydrogel contact lens material according to claim 1, characterized in that, Includes the following steps: (1) Oxygenation mixing of raw materials: After oxygenation, the emulsified perfluorocarbon solution is added to the prepolymer substrate, and the mixture is stirred and oxygenated to make the components evenly mixed to obtain the reaction stock solution; the prepolymer substrate is prepared by mixing hydrophilic monomers and siloxane monomers, and then adding initiator and crosslinking agent and stirring to mix. (2) Curing and molding: Take the original liquid from step (1) and drip it into the concave mold. After UV irradiation, insert the convex mold into the concave mold and continue UV irradiation. After the liquid is completely cured and molded, turn off the UV and let it stand at room temperature. (3) Elution: After standing, the material is demolded, soaked, and extracted with organic solvent to remove unreacted monomers or oligomers, thus obtaining oxygen-carrying silicone hydrogel contact mirror material.

5. The production process according to claim 4, characterized in that, The weight ratio of the hydrophilic monomer to the siloxane monomer in step (1) is 2~5:1~3; the first oxygenation is 10-20 min and the second oxygenation is 30-40 min.

6. The production process according to claim 4, characterized in that, In step (2), the first UV irradiation is 31-40 W for 1-2 min; the second UV irradiation is 31-40 W for 8-10 min.

7. The application of the oxygen-carrying silicone hydrogel contact lens material of claim 1 in the preparation of contact lenses that carry and release oxygen slowly.

Citation Information

Patent Citations

  • Oxygen-permeable fluorosilicone hydrogel contact lens and preparation method thereof

    CN112812243A

  • Silicone hydrogel contact lens

    CN101163991A

  • Silicone Hydrogel Contact Lenses

    CN102323629A